2013
DOI: 10.1007/s40279-013-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intensive Training in the Growth and Maturation of Artistic Gymnasts

Abstract: Short stature and later maturation of youth artistic gymnasts are often attributed to the effects of intensive training from a young age. Given limitations of available data, inadequate specification of training, failure to consider other factors affecting growth and maturation, and failure to address epidemiological criteria for causality, it has not been possible thus far to establish cause–effect relationships between training and the growth and maturation of young artistic gymnasts. In response to this ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1
21

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 82 publications
5
114
1
21
Order By: Relevance
“…us, among the national studies, it was found that there is no standard for the classi cation as elite and non-elite athletes. is research adopted the cuto point of 30 hours of weekly training, as pointed out by review study conducted by M et al 20 . Also, this is a criterion that ts the reality of the Artistic Gymnastics Training Center of Três Rios -RJ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…us, among the national studies, it was found that there is no standard for the classi cation as elite and non-elite athletes. is research adopted the cuto point of 30 hours of weekly training, as pointed out by review study conducted by M et al 20 . Also, this is a criterion that ts the reality of the Artistic Gymnastics Training Center of Três Rios -RJ.…”
Section: Discussionmentioning
confidence: 99%
“…According to M et al 20 , the artistic gymnastics elite athletes training an average of 30 hours per week. is criterion was used as the cuto point for the separation of sample groups in this study.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimum age for participants was 13.0 years at the WC1987 and raised to 16.0 years at the 1997 WC. Mean ages have since increased: 16.5 (WC1987), 17.4 (WC1997), 18.0 (OG2000), and 18.8 (OG2008) years (Claessens, 2001(Claessens, , 2007Malina et al, 2013). The demands of the Olympic gymnastics have continued to escalate, and currently, a light, powerful, and usually, petite athlete is optimal Arkaev and Suchilin (2004).…”
Section: Introductionmentioning
confidence: 99%